Managerial practices as a cause of teacher discomfort in Higher Education: ESCOMP-IPN case - Celis Domínguez, Adriana Berenice (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In Mexican public higher education, the academic continuity within the COVID-19 pandemic has not been smooth. Tension among managers and professors reveal that managerial practices may generate teacher discomfort, although without any clarity in relation to the characteristics of management that provokes it. Through the case study method, the results show that the practice of non collaborative governance and faults in organizational communication represent characteristics of management practices with the capacity to generate resistance in the teaching staff, diminishing the teaching quality in emergency and emergent context.